Pengaruh Efektivitas Sistem Informasi Pengeloaan Keuangan Daerah (SIPKD) Dan Kompetensi Sumber Daya Manusia Terhadap Akuntabilitas APBD Di Kabupaten Bandung Barat - Alya Sahira; Nunung Aini Rahmah (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to find out how the implementation of the Effectiveness of the Regional Financial Management Information System for APBD Accountability in West Bandung Regency with Human Resource Competence. This study uses quantitative data. The analysis technique used in this study was a purposive sampling technique, with 31 samples from 31 populations that were directly related to financial reports. All respondents filled out research questionnaires via googleform. The results of the study show: (1) The effectiveness of the regional financial management information systems have a positive and significant effect on the accountability of the West Bandung Regency APBD. (2) The competence of human resources has a positive and significant effect on the accountability of the West Bandung Regency APBD. (3) The effectiveness of the regional financial management information systems and human resource competencies have a partial or simultaneous effect on the accountability of West Bandung Regency APBD. Keywords: The Effectiveness of the Regional Financial Management Information System (SIPKD), Competence of Human Resources (HR), APBD Accountability